Flipbook-Based E-Module for Thaharah Learning: Modul E-Berbasis Flipbook untuk Pembelajaran Thaharah - Fathurroziq, M. Zidan; Astutik, Anita Puji (Indonesian Journal of Education Methods Development, 2024)
General Background: Effective learning requires meaningful interaction between students and teachers to achieve educational objectives. Specific Background: Students often struggle with traditional teaching materials, necessitating more engaging and interactive resources to foster enthusiasm for learning. Knowledge Gap: There is limited research on the development and application of interactive e-modules, particularly in Islamic Religious Education, to improve student engagement and motivation. Aims: This study aims to develop a flipbook-based e-module for seventh-grade Thaharah material, incorporating features that enhance accessibility and interactivity. Results: The resulting e-module is designed to be user-friendly and portable, featuring engaging content that facilitates learning. It is anticipated that this innovative resource will significantly improve students' abilities and motivation in studying Islamic Religious Education. Novelty: The e-module introduces a unique approach to teaching Thaharah, leveraging the interactive capabilities of flipbooks to enhance the learning experience. Implications: By implementing this flipbook-based e-module, educators can provide a more dynamic and effective learning environment that supports students in their religious education, ultimately leading to improved academic outcomes. Highlights: Interactive Learning: The flipbook-based e-module promotes engagement through interactive features. Portability: The e-module is designed for easy access and mobility, enhancing usability. Motivation Boost: The innovative resource aims to improve students' motivation in Islamic Religious Education. Keywords: e-module, flipbook, Islamic education, Thaharah, student engagement